2020
DOI: 10.4103/2045-9912.289462
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for ozone-therapy as an adjuvant therapy in COVID-19: a narrative review

Abstract: Coronavirus disease 2019 (COVID-19) is the respiratory disease caused by the novel severe acute respiratory syndrome-coronavirus-2 and is characterized by clinical manifestations ranging from mild, flu-like symptoms to severe respiratory insufficiency and multi-organ failure. Patients with more severe symptoms may require intensive care treatments and face a high mortality risk. Also, thrombotic complications such as pulmonary embolisms and disseminated intravascular coagulation are frequent in these patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…In addition, studies on ozone have shown that ozone has an antiviral, antibacterial and disinfectant effect depending on the concentration, environment and application method. 18 19 Ozone therapy refers to the process of applying ozone gas to the body to treat a disease or wound. It can be used to treat medical conditions by stimulating the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies on ozone have shown that ozone has an antiviral, antibacterial and disinfectant effect depending on the concentration, environment and application method. 18 19 Ozone therapy refers to the process of applying ozone gas to the body to treat a disease or wound. It can be used to treat medical conditions by stimulating the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is a disease caused by a novel coronavirus and it can cause a vast array of symptoms, ranging from mild, flu-like symptoms to severe respiratory failure [ 52 ]. Many different therapeutic approaches have been tried, mostly anti-inflammatory therapies, ranging from steroids to antimalaria drugs; even non-conventional therapies, such as ozone-therapy, have been tested [ 53 ]. The most severe symptoms seem to be caused, at least in part, by an autoinflammatory reaction, with characteristics of a cytokine storm [ 52 ]: Binding of the novel coronavirus to TLRs causes an increase in the levels of IL-1β, which mediate fibrosis and inflammation of the lung [ 50 ].…”
Section: Interleukin-6 In Rheumatoid Arthritis and Other Diseasesmentioning
confidence: 99%
“…TÍTULO IDIOMA RESULTADOS (Ranaldi et al, 2020) Rationale for ozone-therapy as an adjuvant therapy in COVID- Nos pacientes que receberam a terapia com ozônio houve uma diminuição da hipóxia tecidual, redução da hipercoagulação, da função imune moduladora com bloqueio de mediadores inflamatórios, aumento da ação fagocítica e diminuição da replicação viral.…”
Section: Autores Anounclassified
“…a indução de interferon gama. Desta forma, esta terapia pode atuar como monoterapia ou como um complemento aos regimes de tratamento padrão, contra a COVID-19(Cattel et al, 2021).Estudo feito porRanaldi et al (2020) constataram que a utilização coadjuvante da ozonioterapia na COVID-19 através da autohemoinfusão ou infusão retal, é capaz de oxigenar melhor os tecidos e equilibrar as reações do sistema imune, pois impede a cascata de liberação de citocinas pelo organismo e regula a microcirculação pulmonar, protegendo e dificultando a hipertrofia muscular, especialmente na fase inicial da infecção pelo vírus.No estudode Cattel et al (2021) foi demonstrado que a terapia com ozônio possui diversos benefícios, entre os quais, previnem as manifestações coronarianas agudas e anomalias ocasionadas pela reperfusão da isquemia. Os autores indicam que o tratamento com ozônio é inovador para a imunoterapia, visto que a sua utilização em associação com outros fármacos antivirais em pacientes infectados com COVID-19 é capaz de torna-se efetivo, benéfico e coadjuvante Shah et al (2021).…”
unclassified